STRUKTUR DAN MAKNA MOTIF BATIK TAMAN ARUM SUNYARAGI - Ari Winarno (ATRAT: Jurnal Seni Rupa, 2013)
General conditions that prevail in place of society have a very strong influence to art that is produced and developed by the region of that particular society, this condition can be proven in Cirebon as a center of Islamic movement carried on as well as a place where cultures from different place meet. These circumstances provide the potential of cultural assimilation as seen on the shape of its batik ornament. The design of batik ornament in Cirebon has many different varieties, but in general it can be categorized into two different designs. The first on in batik Pesisiran, mostly used by common people using contrast colours in a variant design. The second one is batik Pedalaman, this batik is a creation of the Cirebon palace using the some colour appearance with Yogya’s as well as Solo’s batik. Taman Arum Sunyaragi ornament on Cirebon batik is a visual from that evision a garden with contained four massages on the guidance of live. This guidance provides four ways to get closer to God: (1) know yourself, (2) gain knowledge, (3) take control of science, and (4) perform in God’s pathway. This guidance has a closer meaning to Tasawuf in Islam that teaches syari’a, tareka, hakika and ma’rifa.Keywords: Taman Arum Sunyaragi Ornament, Structure, Meaning